KEPEMIMPINAN EFEKTIF KEPALA SEKOLAH DALAM MENGEMBANGKAN PROFESIONALISME GURU - Anizah, Anizah; Maretta, Winda Fitri (Graduate Program Magister Manajemen Pendidikan, 2017)
Education is able to support future development while education could develop the potential of learners in facing global competition. In the educational world, the teachers’ professionalism is needed in order to gain a qualified output. To achieve this goal, principals are very influential in developing teachers’ professionalism. Related to the problem, the purpose of this paper was to know the principal's strategy in developing teachers’ professionalism. The method used in this research was qualitative. To develop the teachers’ professionalism, the principal did organize a portfolio assessment system in the context of teacher’s certification preparation to obtain an certificate educator through Professional Persistence (PKP) in the form of Classroom Action Research (PTK). The expected results, it can develop the teachers’ professionalism in managing the teaching and learning process. Keywords: Effective Leadership, Principal, Teachers’ Professionalism.